Essays on Credit Risk and Credit Derivatives - Claus Bajlum (Copenhagen Business School (CBS), 2008)
This Ph.D. thesis consists of three self-contained chapters, which can be read independently. The chapters are interrelated through their use of structural credit risk models and a credit derivative known as the Credit Default Swap (CDS). Chapter 1 estimates the impact of accounting transparency on the term structure of CDS spreads for a large cross-section of firms. Chapter 2 analyzes the use of CDS spreads in a convergence-type trading strategy known as capital structure arbitrage. Finally Chapter 3 estimates the time-series behaviour of the credit risk premium in the market for Credit Default Swaps.
hdl:10398/6520
Keywords: 650